2019
DOI: 10.31234/osf.io/4qnfk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Goodness of the side of the dominant hand: A registered direct replication of Casasanto (2009)

Abstract: People associate emotional valence with the side of their dominant and non-dominant hands. Specifically, positive (negative) valence is linked with the side of dominant (non-dominant) hand known as the horizontal-valence metaphor. A previous study demonstrated that participants placed a good (bad) object on the side of their dominant (non-dominant) hand (Casasanto, 2009, J. Exp. Psychol.: Gen, 138, 351–367). This phenomenon indicates that the horizontal-valence metaphor influences our behavior. However, subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For instance, gender may play a role in influencing people’s perceptions of power metaphors, with one study finding that male participants were faster to identify powerful groups when they were labeled as male and presented at the top of a computer screen ( Winter et al, 2020 ; see also Charteris-Black, 2012 ; Pérez-Sobrino et al, 2021 ). Handedness may also play a role in metaphoric reasoning: right-handers have been found to make more favorable judgments about objects that are presented on their right-hand side, while left-handers have been found to display more favorable judgments about those presented on their left-hand side ( Casasanto, 2009a ; see also Casasanto and Jasmin, 2010 ; Casasanto and Henetz, 2012 ; but see Sasaki et al, 2019 for contrasting findings in Japanese). Other research has found that metaphorical mappings of morality in space are more prominent among those practicing religion than among atheists ( Li and Cao, 2017 ), suggesting that religious beliefs may likewise play a role in metaphor interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, gender may play a role in influencing people’s perceptions of power metaphors, with one study finding that male participants were faster to identify powerful groups when they were labeled as male and presented at the top of a computer screen ( Winter et al, 2020 ; see also Charteris-Black, 2012 ; Pérez-Sobrino et al, 2021 ). Handedness may also play a role in metaphoric reasoning: right-handers have been found to make more favorable judgments about objects that are presented on their right-hand side, while left-handers have been found to display more favorable judgments about those presented on their left-hand side ( Casasanto, 2009a ; see also Casasanto and Jasmin, 2010 ; Casasanto and Henetz, 2012 ; but see Sasaki et al, 2019 for contrasting findings in Japanese). Other research has found that metaphorical mappings of morality in space are more prominent among those practicing religion than among atheists ( Li and Cao, 2017 ), suggesting that religious beliefs may likewise play a role in metaphor interpretation.…”
Section: Introductionmentioning
confidence: 99%